1978
DOI: 10.1247/csf.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of Cytoplasmic Streaming on Intracellular ATP and Mg<SUP>2+</SUP> Concentrations

Abstract: ABSTRACT.The rate of cytoplasmic streaming (v) The motive force of cytoplasmic streaming in Characeae cells is generated at the boundary between the stationary cortical gel layer and the mobile sol endoplasm (the sol-gel interface). The nature of the motive force is a shearing force produced by the organized gel surface and the sol phase (6). Bundles of microfilaments situated at the surface of the gel phase are assumed to be the component responsible for the generation of the motive force (4,5,12). The fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The ATP-dependent movement of organelles along actin bundles was directly demonstrated in tonoplast-free cells (Williamson 1975;Tazawa et al 1976). Shimmen (1978) showed the hyperbolic relation between ATP concentration and the velocity. He also showed that ADP, orthophosphate, and pyrophosphate inhibited cytoplasmic streaming by competition with ATP, but AMP did not (Shimmen 1988a).…”
Section: Atp As An Energy Sourcementioning
confidence: 99%
“…The ATP-dependent movement of organelles along actin bundles was directly demonstrated in tonoplast-free cells (Williamson 1975;Tazawa et al 1976). Shimmen (1978) showed the hyperbolic relation between ATP concentration and the velocity. He also showed that ADP, orthophosphate, and pyrophosphate inhibited cytoplasmic streaming by competition with ATP, but AMP did not (Shimmen 1988a).…”
Section: Atp As An Energy Sourcementioning
confidence: 99%
“…Cell Sci. 17, 665, 1975), higher concentrations of Ca2+ are inhibitory (Tazawa, Kikuyama and Shimmen, 1976;Shimmen, 1978 ;Hayama, Shimmen and Tazawa, 1979;Hayama and Tazawa, 1980;Kikuyama and Tazawa, 1982;Tominaga, Shimmen and Tazawa, 1983). This is also the case in movement in the myxomycete plasmodium (Yoshimoto, Matsumura and Kamiya, 1981).…”
Section: Dynamics Of Streamingmentioning
confidence: 96%
“…With tonoplast-free internodal cells of Nitella and Chara, Shimmen (1978) showed that the ATP concentration for half saturation of the streaming rate was 0.08 mM in Nitella axillaris and 0.06 mM in Chara corallina. Mg2+ was essential at a concentration equal to, or higher than, that of ATP.…”
Section: Dynamics Of Streamingmentioning
confidence: 99%
“…Since TPF contains only 1 mM ATP, it seemed possible that this inhibition of streaming could have developed because all the ATP had been hydrolyzed by the added enzyme . To mg-' (29) and a HMM concentration of 0.5 mg/ml, then the time required to reduce the ATP concentration from 10 mM to 0 .3 mM (0.3 mM being saturating for streaming [43]) would be -24 min. In perfused Chara cells, however, the only actin available for HMM activation is in the endoplasm-ectoplasm region near the cell periphery.…”
Section: Effect Of Hmm and Fl-hmm On Streamingmentioning
confidence: 99%